(untitled) (International Journal of Engineering and Computer Science, 2017)
The objective of software testing is to deliver a quality and reliable software product to the end user. Testing is an important phase of software development life cycle (SDLC), which is used to trace the errors and to check whether the developed software fulfills the user requirement or not. We require effective software testing, to have reliable software but it is not an easy job, we have to face certain issues like an effective generation of test cases, prioritization of test cases and so on. Different techniques and methodologies have been proposed for taking care of these issues. Genetic Algorithm (GA) is one of the evolutionary algorithms which produce an optimal solution to any problem technique. The aim of the research paper is to implement Genetic Algorithm for minimization of test cases and to reduce cost, time and effort in order to deliver the good quality software